Sādrī : byākaraṇa, racanābaḷī, śabdakosha = Sadri - Paṭela, Paramānanda (Ādibāsī bhāshā adhyayanamāḷā, 1995)
Grammar, composition, and dictionary of the Sadani dialect spoken by local people of Western Orissa.